1990
DOI: 10.1063/1.346457
|View full text |Cite
|
Sign up to set email alerts
|

Reaction between SiC and W, Mo, and Ta at elevated temperatures

Abstract: The stability of W, Mo, and Ta in contact with single-crystal β-SiC at elevated temperatures has been investigated using Auger sputter profiling. All three metals were found to form a thin-mixed layer of metal carbide and silicide upon metal deposition at room temperature. This layer is thought to be the result of surface defects which weaken the Si—C bonds and allow a low-temperature reaction to occur. Upon heating, the Ta readily reacts with the SiC substrate and forms a mixed layer of Ta carbide and silicid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 23 publications
3
33
0
Order By: Relevance
“…In line with the explanation given by Geib et al [20], the reaction between W and SiC on our as-deposited samples might be due to the Ar plasma cleaning before deposition. The presence of a silicide and a carbide on the as-deposited is due to the favourable kinetic and thermodynamic factors at the interface.…”
Section: Sem Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…In line with the explanation given by Geib et al [20], the reaction between W and SiC on our as-deposited samples might be due to the Ar plasma cleaning before deposition. The presence of a silicide and a carbide on the as-deposited is due to the favourable kinetic and thermodynamic factors at the interface.…”
Section: Sem Resultssupporting
confidence: 69%
“…The reaction between W and SiC during deposition was also reported in earlier studies done by Geib et al [20], in which they sputter deposited W on SiC. Their resulting Auger profiles for the as-deposited sample showed that a reaction between W and SiC took place to form WSi 2 and WC.…”
Section: Sem Resultsmentioning
confidence: 51%
“…This preferential etching of silicon from SiC surface leading to the formation of a carbon-rich surface layer by a RF plasma process by low energy (0.5 to 5 keV) argon ion bombardment has been observed to occur before in. [34][35][36] The deposition of Zr creates an intermixing effect between Zr and C which resulted in the formation of ZrC on the as-deposited sample as observed from XRD results. Transition metals such as W, Mo and Ta have been observed form a thin intermixed layer of carbide and silicide aer deposition at room temperature.…”
mentioning
confidence: 89%
“…W films with thickness less than 100 nm resulted in the formation of WSi 2 [27]. In our case we deposited W thin film of 65 nm on SiC which resulted in the formation of WSi 2 silicide.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%